2017
DOI: 10.1680/jtran.16.00012
|View full text |Cite
|
Sign up to set email alerts
|

Teenage trespass on the railways – a systems approach

Abstract: Rail trespass and risk-taking behaviours are particularly high among 16-25 year olds. The aim of the research described in this paper is to understand how the communication of safety information to these groups can be improved. The study involves focus groups with 117 young people and 43 interviews with stakeholders drawn from the rail industry alongside professionals involved in working with young people. Participants in the focus groups are shown a set of four safety videos which describe the dangers of tres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…The results showed that education should be realistic, accurate, and clear to understand for all involved with the use of social networks to reach a wider audience. Furthermore, education can start as early as 6 to 7 years old, and be incorporated into the school curriculum [69]. The same was suggested in another study, but for children aged 8 to 11 years old, in that trespassing can be reduced by implementing railway safety into the school curriculum using different teaching materials, educating parents, and combining education measures with other preventive measures [70].…”
Section: Educational Measuresmentioning
confidence: 99%
“…The results showed that education should be realistic, accurate, and clear to understand for all involved with the use of social networks to reach a wider audience. Furthermore, education can start as early as 6 to 7 years old, and be incorporated into the school curriculum [69]. The same was suggested in another study, but for children aged 8 to 11 years old, in that trespassing can be reduced by implementing railway safety into the school curriculum using different teaching materials, educating parents, and combining education measures with other preventive measures [70].…”
Section: Educational Measuresmentioning
confidence: 99%